2022
DOI: 10.3390/cancers14040985
|View full text |Cite
|
Sign up to set email alerts
|

Current Limitations and Novel Perspectives in Pancreatic Cancer Treatment

Abstract: Pancreatic cancer is one of the deadliest cancers worldwide, largely due to its aggressive development. Consequently, treatment options are often palliative, as only one-fifth of patients present with potentially curable tumors. The only available treatment with curative intent is surgery followed by adjuvant chemotherapy. However, even for patients that are eligible for surgery, the 5-year OS remains below 10%. Hence, there is an urgent need to find new therapeutic regimens. In the first part of this review, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 161 publications
0
30
0
Order By: Relevance
“…Some studies suggested that the low count of dendric cells in the pancreatic tumour environment is the reason behind the low response to immunotherapy [ 53 ]. Although Pembrolizumab was approved by the FDA as an anti-programmed death-1 (PD-1) inhibitor for advanced PDAC, unfortunately, its effectiveness is limited to less than 1% of patients [ 64 , 65 , 66 ].…”
Section: Overview Of Pancreatic Cancermentioning
confidence: 99%
“…Some studies suggested that the low count of dendric cells in the pancreatic tumour environment is the reason behind the low response to immunotherapy [ 53 ]. Although Pembrolizumab was approved by the FDA as an anti-programmed death-1 (PD-1) inhibitor for advanced PDAC, unfortunately, its effectiveness is limited to less than 1% of patients [ 64 , 65 , 66 ].…”
Section: Overview Of Pancreatic Cancermentioning
confidence: 99%
“…The viability of isolated cancer tissue samples is relatively low, largely due to local environmental factors. Moreover, various treatments such as neoadjuvant chemo- or radio-therapy have an impact on cell viability [ 2 ]. Successful scRNA-seq requires removal of dead cells [ 3 ] and debris, so isolation of as many live cells as possible from the initial sample is beneficial [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the International Association of Pancreatology (IAP) introduced the ABC criteria that determine the resectability, not only on the localization regarding the blood vessels but also by incorporating the ECOG status, the lymph node status, as well as tumor markers. This underlines the complexity of determining valid protocols for the resectability of PDAC [ 3 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%